The Impact of FinTech in Risk Management on Banks - Cui, Yuhang (Transactions on Economics, Business and Management Research, 2024)
Many financial institutions are involved in the FinTech as the improvement of FinTech. FinTech has a big influence in every area of economics, economy, or the bank. The FinTech has many advantages for financial institutions. FinTech provides high productivity for financial institutions and helps them avoid and solve many problems that they will face. The goal of this paper is to find out the relationship and influence between the FinTech and a special financial institution—a bank. This paper analyzes the different influences on the different parts of the bank business, especially the impact on the risk management in the bank. The creation and development have a huge influence on the present financial and economy. Especially compared to traditional financial, FinTech helps financial institutions to reach a level that traditional financial never achieve. But FinTech has both benefits and risks. The security of FinTech is a major concern for financial institutions around the world.